Manifestasi Kulit pada COVID-19; Pengulasan - Syifa Rahmi Fadhila; Winda Trijayanthi (CV. Jasa Sukses Abadi, 2021)
COVID-19 is a respiratory infection caused by the coronavirus. The main target of this virus attacks the mucosa of the upper respiratory tract and angiotensin-converting enzyme (ACE2) which is the receptor for viral entry. COVID-19 has many clinical manifestations. The clinical manifestations that appear in COVID-19 patients are similar to other respiratory viral infections, such as high fever, dry cough. However, over time there are many other manifestations such as fever, dry cough, diarrhea, shortness of breath (dyspnea), ageusia, anosmia, and the onset of skin manifestations. This article discusses skin manifestations in COVID-19 patients based on literature studies. The research method used in this journal is literature review. The author is looking for literature related to the topics discussed in this journal. From the research results, the skin can appear within 3 days before being diagnosed up to 13 days after being diagnosed with COVID-19. In the case of positive Covid-19 asymptomatic patients, clinical manifestations will appear on the 14th day and can be used as indicators of diagnosis. The most common skin manifestation that appears in COVID-19 patients is a maculopapular rash. Other lesions that can occur in COVID-19 patients, especially in young adults to the elderly, are urticaria, erythema nodosum, vesicular rash, petechiae / purpuric rash.